TECHNOLOGICAL QUALITIES AND PRODUCTIVITY OF HARD WINTER WHEAT GRAIN DEPENDING ON USE OF BIOLOGICALLY ACTIVE PREPARATIONS - Yarchuk, I. I.; Melnyk, T. V.; Chernykh, S. A. (Scientific Progress & Innovations, 2021)
The need for hard wheat grain is approximately a million ton for Ukraine per year. However, such amount of grain is not produced in the country, that’s why a significant volume of grain and ready products are bought in other countries. Of course, this case cannot be considered normal especially taking into account the fact that Ukraine has one of the best soil and climatic conditions for growing wheat. The article deals with the results of field studies of biologically active preparations’ influence on the productivity and technological qualities of hard winter wheat in the conditions of the Northern Steppe. The experiments (2014–2017) were held on the black fallow land at two mineral fertilization backgrounds: Р15 + N30 and N30P60K40 + N30 at cultivating Continent winter hard wheat using such preparations as AKM, Antistress, Biohumus (granulated), Vympel, Mars ELBi, Reacom-CP-zerno, Chlormekvat-chloride 750 at different application time with the dosages recommended by their producers. It was established that during the years of the study the highest yield increase was observed at using the preparations AKM (autumn) – 1.45 t/ha and Mars ELBi (spring) – 1.34 t/ha. Positive results were also received at applying AKM (spring) – the increase made 1.16 t/ha, Chlormekvat-chloride 750 (spring) – 0.71 t/ha and Biohumus + Aidar – 0.71 t/ha. In contrast to the low mineral fertilization background (Р15 + N30), the high mineral fertilization background (N30P60K40 + N30) was not effective. Chlormekvat-chloride 750 preparation showed the positive effect only in the conditions of high agricultural background. AKM preparation at spring fertilization constantly increased the yield at all variants of agricultural background but best of all under the low level of mineral fertilization. Among the studied preparations, the greatest stability in hard wheat grain productivity was demonstrated by Mars ELBi used in spring after the spring vegetation recovery (at average day temperature +10 оС) with the rate of 750 ml/ha. The grain quality varied a lot during the years of studies: in 2016, with the lowest yields, protein content in the majority of variants was the highest. Among the studied preparations in dry 2016, independently of the level of mineral fertilization, the following preparations were effective: Antistress, AKM, Biohumus + Aidar, Chlormekvat-chloride 750. And in 2014, a relatively favorable year, only at Biohumus + Aidar and Reacom-CP-zerno application at the low background and Mars ELBi application at the high background, the grain could be classified as the first class by protein content. The rest of the preparations did not improve the grain quality; by the protein content the grain could be classified as the 3rd and even 4th class.